Numerical simulation of particle motion in dense phase pneumatic conveying - Xiang,J; McGlinchey,D (Granular Matter, 2004)
A gas-solids two-dimensional mathematical model was developed for plug flow of cohesionless particles in a horizontal pipeline in dense phase pneumatic conveying. The model was developed based on the discrete element method (DEM). For the gas phase, the Navier-Stokes equations were integrated by the semi-implicit method for pressure-linked equations (SIMPLE) scheme of Patankar employing the staggered grid system. For the particle motion the Newtonian equations of motion of individual particles were integrated, where repulsive and damping forces for particle collision, the gravity force, and the drag force were taken into account. For particle contact, a nonlinear spring and dash pot model for both normal and tangential components was used. In order to get more realistic results, the model uses realistic pneumatic system and material values. (8 refs.)